Upconversion nanoparticles and its based photodynamic therapy for antibacterial applications: A state-of-the-art review - Lv, Hanlin; Liu, Jie; Wang, Ying; Xia, Xiaomin; Li, Ying; Hou, Wenxue; Li, Feng; Guo, Lantian; Li, Xue (Frontiers in Chemistry, 2022)
Major medical advances in antibiotics for infectious diseases have dramatically improved the quality of life and greatly increased life expectancy. Nevertheless, the widespread and inappropriate exploitation of antibacterial agents resulted in the emergence of multi-drug resistant bacteria (MDR). Consequently, the study of new drugs for the treatment of diseases associated with multi-drug resistant bacteria and the development of new treatments are urgently needed. Inspiringly, due to the advantages of wide antimicrobial spectrum, fast sterilization, low resistance, and little damage to host tissues and normal flora, Antibacterial Photodynamic Therapy (APDT) which is based on the interaction between light and a nontoxic photosensitizer (PS) concentrated at the lesion site to generate reactive oxygen species (ROS) has become one of the most promising antibacterial strategies. Recently, a burgeoning APDT based on a variety of up-conversion nanoparticles (UCNPs) as PS and near-infrared (NIR)light has been fully integrated in antibacterial applications and achieved excellent performances. Meanwhile, conjugated nanoparticles have been frequently reported in UCNPs design, including surface modified PS conjugates, antibiotic-PS conjugates, and dual or multiple antibacterial modal PS conjugates etc. This article provides an overview of the state-of-the-art design and bactericidal effects of UCNPs and their based APDT. The first part discusses the design and mechanisms for UCNPs currently implemented in biomedicine. The second part focuses on the applications and antimicrobial effects of diverse APDT based on UCNPs in antibacterial-related infectious diseases. In addition, the future perspectives of UCNPs and its based APDT will be discussed at the end of this review.